Liquidity Preference Theory or Loanable Funds Theory - Jossa, Bruno (Archives of Business Research, 2021)
In Keynes’s approach, interest rates are driven up by rises in demand for money and scaled down by rises in money supply. On the contrary, this paper argues that neither of these propositions will stand the test of scrutiny. Keynes traced demand for money to three main factors, the transaction, precautionary and speculative motives, but rises in demand associated with the transaction motive do not necessarily drive up the rate of interest. The paper shows also that the liquidity preference theory and the loanable funds theory are different theories and that the former is faulty, while the latter is correct.